Historical encyclopedia of U.S. independent counsel investigations - Greenberg, Gerald S. (Gale virtual reference library., 2000)
A compilation of the U.S. federal special prosecutor/independent counsel investigations spanning the complete twenty-one year tenure from 1978-1999 of the independent counsel statute.